The development and validation of Malaysian secondary school student's leadership inventory - Ling, Mei Teng (2016)
Leadership skill is one of the elements that is emphasised in the Malaysian Education Development Plan 2013-2025. A valid and reliable scale to measure leadership among secondary school students is still unavailable in schools and student leadership is not specifically evaluated in schools. This study aimed to develop the Malaysian Secondary School Students’ Leadership Inventory (M3SLI) and to determine the related psychometric properties by using the Rasch Rating Scale Measurement Model and Hierarchical Component Model (HCM). In an effort to develop a new instrument, Design and Development Research (DDR) design provides the basis for this research design. The newly developed questionnaire was administered to 2340 students from 26 schools in four main divisions of Sabah. The validity and reliability of the M3SLI are acceptable to measure the leadership potential of secondary school students. The evidence of Differential Item Functioning (DIF) does not exist, indicates that personality, values and competencies constructs in M3SLI function similarly on different genders, school locations and forms. There are no collinearity issues in formative indicators and first order components and all the outer weight are significant. The item-person map confirmed the predictive validity of M3SLI. Eight types of leaders were proposed in this study based on their personalities, values and competencies. Re-testing of the instrument and improvement of items have to be applied before the measurement scale of M3SLI can be used as an established instrument. School administrators should be based on the student leadership profile when come to selecting head prefect or any other important leadership positions in school.